Social and Emotional Processing as a Behavioural Endophenotype in Eating Disorders: A Pilot Investigation in Twins. (7th May 2013) - Kanakam, Natalie; Krug, Isabel; Raoult, Charlotte; Collier, David; Treasure, Janet
Abstract: Objectives: Emotional processing difficulties are potential risk markers for eating disorders that are also present after recovery. The aim of this study was to examine these traits in twins with eating disorders. Methods: The Reading the Mind in the Eyes test, Emotional Stroop task and the Difficulties in Emotion Regulation Scale were administered to 112 twins with and without eating disorders (DSM IV‐TR eating disorder criteria). Generalised estimating equations compared twins with eating disorders against unaffected co‐twins and control twins, and within‐pair correlations were calculated for clinical monozygotic ( n  = 50) and dizygotic twins ( n  = 20). Results: Emotion recognition difficulties, attentional biases to social threat and difficulties in emotion regulation were greater in twins with eating disorders, and some were present in their unaffected twin siblings. Evidence for a possible genetic basis was highest for emotion recognition and attentional biases to social stimuli. Conclusion: Emotion recognition difficulties and sensitivity to social threat appear to be endophenotypes associated with eating disorders. However, the limited statistical power means that these findings are tentative and require further replication. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.